Quantitative Diffusion-Weighted MRI of Neuroblastoma - Abele, Niklas; Langner, Soenke; Felbor, Ute; Lode, Holger; Hosten, Norbert (Cancers, 2023)
In this study quantified diffusion weitgthed imaging in MRI was analized in neuroblastoma. We were able to show a significant increase of apparent diffusion coefficient in regressive diseases and a decrease for progressive diseases. This was even true within the first 120 days after the start of therapy.
CRIS-Team WoS Importer:2023-05-12